Metaphors In Illocutive Speech Acts: A CrossCultural Pragmatic Comparison Between English And Uzbek (The Peerian Journal, 2025)
The article explores the role of metaphors to represent socio-pragmatic aspects of illocutionary speech acts in English and Uzbek languages. The work is based on comparative analysis of metaphors in both languages which concentrated on apologies, complaints, offers and invitations among other types of illocutive speech acts. The article is aimed at to highlight the differences and similarities between these languages in terms of the usage of metaphors to demonstrate certain social and pragmatic aspects of these nations.